Aldolase B mutations in Italian families affected by hereditary fructose intolerance. Issue 4 (April 1991) - Sebastio, G; de Franchis, R; Strisciuglio, P; Andria, G; Dionisi Vici, C; Sabetta, G; Gatti, R; Cross, N C; Cox, T M
Abstract : Hereditary fructose intolerance (HFI) is an inborn error of metabolism caused by aldolase B deficiency. The aldolase B gene has been cloned and the following mutations causing HFI have been identified: A149P (a G----C transversion in exon 5), A174D (a C----A transversion in exon 5), L288 delta C (a base pair deletion in exon 8), and N334K (a G----C transversion in exon 9). We have investigated the occurrence of these mutations in 11 Italian patients affected by HFI using PCR and hybridisation to specific oligomers. We found that four patients were homozygous for the A149P mutation, two patients were homozygous for the A174D mutation, three patients were compound heterozygotes for both the A149P and A174D mutations, one patient was homozygous for the N334K mutation, and one patient did not show any of the reported mutations (HFI diagnosis carried out by aldolase B assay). The L288 delta C mutation has not been found in this survey.